STRATEGI GERAKAN WOMEN OF KRUSHA SEBAGAI INISIATOR NGO FEMINIS DAN PEMBERDAYAAN PEREMPUAN PASCA KONFLIK DI KOSOVO TAHUN 1999-2008 - Yossienta Amelia Puspitasari (HI 16 UMY 192, 2016)
*192 This research focus on the Women of Krusha movement which become initiator of Feminism NGO in Kosovo and its contribution for women empowerment of the post conflict era in Kosovo. With a qualitative approach, this research emphasizes the content analysis method. Framework in this research departs from High Level Politics Approach: Grassroot Mobilization and High Level Partnership Approach: Grassroot Development. The issue of women and women's empowerment in post-conflict has become one interesting issues in the realm of international relations. Ethnicity –based war and conflict in post-conflict Kosovo left the trauma and deep psychological burden for civil society in Kosovo, especially the women. Large-scale massacres of ethnic Albanian men in the village of Krusha, Kosovo force women to live independently and start a new life as well as the initiator for their environment. Women movement in Kosovo show us that feminism is not only ideological but also the empowerment of women both physically and mentally in many aspects of their life.